Peranan Badan Permusyawaratan Desa (BPD) Dalam Upaya Optimalisasi Perencanaan Pembangunan Desa Di Desa Riit Kecamatan Nita Kabupaten Sikka - Yohana Nirmala Daung; Petrus Kpalet; Rudolfus Ali (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
This study aims to determine the condition of the Role of the Village Consultative Body in Optimizing Village Development Planning in Riit Village, Sikka Regency and to find out the efforts of the Role of the Village Consultative Body in Optimizing Village Development Planning. And also aims to find out the driving and inhibiting factors for village development planning. fast. This study uses a qualitative method. while the data collection techniques used were observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and data verification. The results of the study show that the role of partners between village consultative bodies within the village government apparatus, moreover, the relationship between the Village Consultative Body (BPD) is compatible and well-established, transparent, and there is no cover-up from the two parties. All matters of government and The problems faced together in village deliberations (MUSDES) are seen from the community's point of view, the role of village consultative bodies has been going well but not optimal because of the lack of socialization from members of the village consultative bodies.